Vegetable Oil‐Based Waterborne Polyurethane as Eco‐Binders for Sulfur Cathodes in Lithium–Sulfur Batteries. Issue 19 (6th August 2021) - Chen, Zhuzuan; Man, Limin; Liu, Ju; Lu, Liangmei; Yang, Zhuohong; Yang, Yu
Abstract: Lithium–sulfur batteries (LSBs) suffer from well‐known fast capacity losses despite their extremely high theoretical capacity and energy density. These losses are caused by dissolution of lithium polysulfide (LiPS) in ether‐based electrolytes and have become the main bottleneck to widespread applications of LSBs. Therefore, there is a significant need for electrode materials that have a strong adsorption capacity for LiPS. Herein, a waterborne polyurethane (WPUN) containing sulfamic acid (NH2 SO3 H) polymer is designed and synthesized as an aqueous‐based, ecofriendly binder by neutralizing sulfamic acid with a tung oil‐based polyurethane prepolymer. UV–vis spectroscopy shows that the WPUN strongly immobilizes LiPS and thus is an effective inhibitor of the LiPS. Moreover, the WPUN binder has excellent adhesive and mechanical properties that improve the integrity of sulfur cathodes. The WPUN‐based cathodes exhibit a significant improvement in their specific capacity and maintain a capacity of 617 mAh g −1 after 200 cycles at 0.5C. Besides, the LSBs assembled with the WPUN‐based cathodes show good rate performance from 0.2C (737 mAh g −1 ) to 4C (586 mAh g −1 ), which is significantly higher than that of LSBs assembled with a commercial polymer binder. The structural design of the presented binder provides a new perspective for obtaining high‐performance LSBs. Abstract : The structural design of the waterborne polyurethane (WPUN) binder is rich in polar groups, including sulfonic acid groups, urethane groups, and quaternary ammonium groups that provide sufficient active sites that can anchor soluble polysulfides. The long chain fatty acids in the WPUN‐binder prevent the collapse of the electrode structure that is caused by the volume expansion during the cycles.